Association between Disease Severity and Coagulation Profile in Lung Cancer Patients - Faiz Ahmed Faiz, Sidra Izhar, Muhammad Fahad Faiz, (Pakistan Journal of Medical & Health Sciences, 2023)
The main idea behind this study is to assess the extent of derangement of coagulation parameters, prothrombin time (PT) and activated partial thromboplastin time (APTT), in lung cancer as occurrence of these abnormalities may be associated with excessive bleeding. Objectives: To find out the association between disease severity and coagulation profile in lung cancer patients. Materials & Methods: Sixty patients with lung cancer were included in the study from pulmonology department, Allama Iqbal Memorial Teaching Hospital, Sialkot. Two groups were formed from the chosen patients. 15 healthy, age- and sex-matched controls were included in group A, while 45 patients with a histological diagnosis of lung cancer were included in group B. There was no history of coagulation disorders or anti-coagulant therapy in selected patients. PT, APTT, Fibrinogen, FDP’s were recorded. Result: The median age was 49 years (range from 13 to 62 years) with male to female ratio of 1.8:1.Among them, 70% of lung cancer patients had history of smoking and 17.77% had stage lb, 22.22% had llb, 8.88 % llla, 33.33 lllb, 17.77 % had stage lV disease. Histologic sub-type were Non-small cell lung cancer (NSCLC) 40 %, Small cell lung cancer (SCLC) were 13.3 %, Squamous cell cancer were 33.33 %, adenocarcinoma 11.1 % and large cells cancer were 2.2 %. The Mean ± SD value for these respective groups were PT (Sec) 15.16±3.8 and 12.4±0.1, for APTT (Sec) 37.7±4.9 and 25.26±1, for Fibrinogen (mg/dl) 299.5±33.6 and 285.3±43.65 respectively. Quantitative estimation of FDPs were done in all. Elevated levels of FDP (≥ 10 µgm/mL) were found in 23 patients. Conclusions: High coagulation parameter levels were linked to advance cancer staging, according to this study, and these parameters may be utilised to forecast how severe a patient's lung cancer will be. Keywords: Disease Severity, Lung Cancer, coagulation disorders